Методи обробки сигналів та зображень - Телятников, Г. А. (ХНУРЕ, 2025)
The development of signal and image processing methods plays a crucial role in modern technology, impacting areas such as medical imaging, telecommunications, remote sensing, and artificial intelligence. Advanced algorithms, including wavelet transforms, Fourier analysis, and machine learning techniques, enhance signal clarity, noise reduction, and feature extraction. In medical diagnostics, image processing improves the accuracy of disease detection through MRI and CT scan enhancements. In telecommunications, adaptive filtering and compression techniques ensure efficient data transmission. This study explores the latest advancements in signal and image processing, emphasizing their applications in various industries and future prospects for technological improvement.
Keywords: обробка сигналів; обробка зображень